Evaluation of caesarean deliveries using the modified Robson’s classification: a prospective observational study at a tertiary care hospital - Dass, Amar; Gupta, Amit; Chauhan, Vikrant; Sharma, Sachin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Caesarean section (CS) is one of the most frequently performed obstetric procedures, crucial for reducing maternal and perinatal morbidity and mortality when indicated. However, rising global and national CS rates, surpassing the World Health Organization’s recommended 10-15%, have raised concerns about potential overuse. The Robson Ten-Group Classification System (RTGCS) provides a standardized method for auditing and analyzing CS rates. This study aimed to determine the caesarean section rate and identify the Robson groups contributing most to CS rates at a tertiary care hospital in Himachal Pradesh. Methods: In the Department of Gynecology and obstetrics at Dr. R.P.G.M.C., Kangra (Tanda), a prospective observational study was performed, spanning from May 1, 2024 to October 31, 2024. The study included all pregnant women at 28 weeks of gestation or more who underwent cesarean section. Participants were categorized into ten groups based on the modified Robson classification system. Real-time data collection was followed by statistical analysis using SPSS version 27. Chi-square test was applied, with p<0.05 considered statistically significant. Results: Among 3755 deliveries, 1296 were caesarean sections, yielding a CS rate of 34.51%. Group 5 (previous CS, singleton, cephalic, ≥37 weeks) was the leading contributor (30.4%), followed by Group 2 (24.5%) and Group 1 (14.5%). Groups 6 and 10 contributed 7.9% and 6.9%, respectively. Conclusions: The study highlights a high CS rate, with repeat and primary caesareans in low-risk groups as major contributors. Targeted strategies, including reducing primary CS, promoting vaginal birth after caesarean (VBAC), and adopting standardized labour management protocols, are urgently needed.